FORMATION AND DEVELOPMENT FACTORS IN THE DIGITAL EDUCATION PROCESS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In this essay, we will discuss how the transition to digital education will drastically alter the professional activities of educators and service workers in the higher education and training system. Pedagogical technologies that emerged throughout the digitalization process create new circumstances for student activity and competency creation; today, digitalization of the education system is one of the most pressing challenges.